FAKTOR-FAKTOR YANG MEMPENGARUHI AKUNTABILITAS PEMERINTAH DAERAH (Studi Komparatif Pemerintah Kabupaten Bantul dan Kabupaten Sleman) - Mochammad IqbalFadhlurrohman; Budiman; Etika Khairina (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The results of the performance carried out by the government require an accountability report from the government in order to see the success made by the government in carrying out the performance which is to make the community prosperous. In this study, it looks at what are the factors that influence the performance accountability process of government agencies and the factors seen in this study, namely from organizational culture and compliance with laws. In this study using qualitative analysis which is assisted by analysis using Nvivo12 plus. The results of this research using Nvivo12 plus are that in two related institutions the results are different, such as in Bappeda Sleman the factors used by organizational culture are very significant, namely 66% of the influence on the performance accountability process of government agencies and for compliance with legislation the effect is 33%. And for the Bantul secretariat itself from the organizational culture, namely 58% influence on the organizational performance accountability process and for compliance with legislation, namely 41% influence in the organizational performance accountability process. So in this research, from the two factors that influence the process of organizational performance accountability, it can be seen that quite significant results from these two factors can affect the results of performance accountability which makes the performance process increase in its implementation